The impact of COVID-19 measures on health-related outcomes in people with dementia: A systematic review of reviews - Amelia Davies; Aysegul Humeyra Kafadar; Katy A Jones (Cogent Gerontology)
The COVID-19 pandemic led to nations worldwide implementing measures to prevent the spread of the virus. Dementia is a leading cause of death globally. People with dementia were particularly vulnerable to the measures implemented during the pandemic. To explore the health-related impact of pandemic restriction measures on people with dementia. A systematic search of four databases (PubMed, PROSPERO, EMBASE and Cochrane Library) was conducted (November 2023, and November 2024). The PRISMA Checklist 2020 was used for quality checking. Extracted data were analysed using narrative analysis. Seventeen reviews were included in the qualitative synthesis. All the included reviews reported a decline in different health-related outcomes of people with dementia due to COVID-19 pandemic restrictions. Fourteen reviews reported effects on psychological outcomes, 13 showed worsening of cognitive function, and 12 showed worsening of behavioural symptoms. Seven reviews reported a decline in physical outcomes and one reported increased mortality rate. Overall, there was a general decline in health-related outcomes of people with dementia during theCOVID-19 pandemic associated with the restriction measures put in place. Further research should examine how to overcome issues resulting from the restrictions, such as loneliness, to improve health-related outcomes for people with dementia.